ANALYSIS OF SOCIAL MEDIA ON STUDENT LEARNING MOTIVATION IN INDONESIAN LANGUAGE SUBJECT AT SERANG 06 PUBLIC PRIMARY SCHOOL - Suryawan, Awi; Nursehah, Uvia; Dzil Ikrom, Fadhli (LPPM Universitas Bina Bangsa, 2026)
This study aims to: Determine how big the role of social media is on the motivation to learn Indonesian at Serang 06 State Elementary School. The type of research that will be used when conducting research is qualitative research with studies or studies that focus on certain cases, so that researchers hope to obtain relatively complete and in-depth data, and can also be interpreted on various phenomena encountered in the field. The results of the study show that social media as a learning tool can make it easier for students to understand the material related to the theme being studied. This is proven by the results of observations and questionnaires with the results After Using Social Media 32 out of 38 students (84.2%) always try to sit in the front when Indonesian lessons involve social media. 30 out of 38 students (78.9%) always study and work on questions that have not been taught for the next meeting. Then 32 out of 38 students (84.2%) feel happy when Indonesian class time arrives. 28 out of 38 students (73.7%) do their homework or Indonesian assignments early. 30 out of 38 students (78.9%) get good grades and are satisfied with the grades obtained in Indonesian lessons. 32 out of 38 students (84.2%) try to understand and study extra for Indonesian lessons.